2018
DOI: 10.11607/jomi.6419
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Esthetic Outcome of Tissue-Level and Bone-Level Implants in the Anterior Maxilla

Abstract: Within the limits of this study, it can be stated that both implant designs showed comparably satisfying esthetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…Over time there has been a shift in the use of tissue‐level implants to bone‐level implants. Bone‐level implants can enable the practitioner to create a natural emergence profile with individually designed abutments, which is particularly useful in the aesthetic zone (Chappuis, Bornstein, Buser, Belser, ; Siebert, Rieder, Eggert, Wichmann, Heckmann, ). A satisfying treatment outcome should be durable and stay stable for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Over time there has been a shift in the use of tissue‐level implants to bone‐level implants. Bone‐level implants can enable the practitioner to create a natural emergence profile with individually designed abutments, which is particularly useful in the aesthetic zone (Chappuis, Bornstein, Buser, Belser, ; Siebert, Rieder, Eggert, Wichmann, Heckmann, ). A satisfying treatment outcome should be durable and stay stable for many years.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the strains induced by the soft tissue level implant are higher in both load scenarios, this type of implant has shown excellent conservation of the marginal bone in clinical studies and has been used even as the control for marginal bone loss in animal trials (Heitz-Mayfield et al 2013). In the clinical practice, both implants have also shown comparable long-term esthetic outcomes where the marginal bone level plays a critical role (Siebert et al 2018). This could suggest, that the higher strains induced by the soft tissue level implant are still within the physiological range to preserve the marginal cortical bone and avoid resorption.…”
Section: Resultsmentioning
confidence: 90%
“…Retrospective data suggest that one-part and two-part implants presented comparable treatment outcomes in terms of mesial and distal papilla heights over a mean follow-up period of 3.7 years and 9.5 years, respectively. 47 Regarding the design of the implantabutment junction, findings from a randomized clinical study demonstrated that implants with nonmatching implant-abutment interfaces (platform-switch design) experienced a gain in the papilla height during the 2-year follow-up period, whereas the interproximal papilla showed apical migration at the implants with matching implant-abutment connections (+0.18 mm and −0.88 mm, respectively; P ≤ 0.005). 48…”
Section: Implant Designmentioning
confidence: 99%